Incremental Mapping Compilation in an Object-to-Relational Mapping System (Extended Version) - Bernstein, Phil; Jacob, Marie; Perez, Jorge; Rull, Guillem; Terwilliger, James (2013)
In an object-to-relational mapping system (ORM), mapping expressions explain how to expose relational data as objects and how to store objects in tables. If mappings are sufficiently expressive, then it is possible to define lossy mappings. If a user updates an object, stores it in the database based on a lossy mapping, and then retrieves the object from the database, the user might get a different result than the updated state of the object; that is, the mapping might not “roundtrip." To avoid this, the ORM should validate that user-defined mappings roundtrip the data. However, this problem is NP-hard, so mapping validation can be very slow for large or complex mappings. We circumvent this problem by developing an incremental compiler for OR mappings. Given a validated mapping, a modification to the object schema is compiled into incremental modifications of the mapping. We define the problem formally, present algorithms to solve it for Microsoft’s Entity Framework, and report on an implementation. For some mappings, incremental compilation is over 100 times faster than a full mapping compilation, in one case dropping from 8 hours to 50 seconds. This is an extended version of a paper that appears in the SIGMOD 2013 Conference.